MORAL MESSAGE IN ALIF AND ALYA’S ANIMATED FILM ”EPISODE 1-4” AS CHILDREN’S EDUCATION (RONALD BARTHES SEMIOTICS ANALYSIS) - Ali Iskandar Zulkarnain; S Surawan; Siti Nur Wahidah (Profetika: Jurnal Studi Islam, 2022)
Children are the younger generation as human resources to succeed in the ideals of the nation’s struggle and the need for intellectual and moral intelligence in building national progress. One of the factors that shape children’s morals is what children see. This study aims to describe the form of moral messages contained in the animated film Alif and Alya “Episode 1-4”. The method used in this study is a qualitative descriptive method using the semiotic analysis of Ronald Barthes’ theory. Data collection techniques through documentation, research data search through scenarios (film scripts, pictures, or film clips) from the animated cartoon Alif and Alya “episode 1-4”. The results of the research in Alif and Alya’s animated show “episode 1-4” highlight good morals that can be imitated by children, including 1) It contains several moral messages, including caring, kindness, helping, cooperation, patience, devoted to parents, praying, tolerance, maintaining health, friendly, honest, and grateful, 2) The moral message contained in Alif and Alya’s animated show “episode 1-4” has many meanings, divided into several scenes where the model Ronald Barthes’ semiotic analysis uses the concept of denotative meaning, connotative meaning, and myth to get the meaning of the moral message contained in Alif and Alya’s animated show “episode 1-4”.